Learning makhraj for children by 3D visualization / Najhan Pata Sairi - Pata Sairi, Najhan (2009)
Learning pronunciation with multimedia element is one of the teaching pedagogy in improving the pronunciations. In language development, it is also a practical tool and useful in learning especially to children. The objectives of our research/project are to show the movement in Makhraj Pronunciation and to develop a 3D visualization for Makhraj Pronunciation. Makhraj is the correct position of organs of speech in order to produce a letter so that it can be differentiated from others. The children just know how to pronounce the Arabic letter but not properly in the Makhraj pronunciation. The project will use 3D visualization and 2D animation to show the Makhraj pronunciation with correct voice and movement in Makhraj pronunciation.